(untitled) (Research, Society and Development, 2020)
This article will analyze the context of judicialization of urban public policies in the Municipality of Niteroi (RJ), since in this territoriality there is a scenario prone to judicialization of urban public policies, resulting in a technocratic process based on strategic planning and actions due to the implementation of mechanisms and strategies that effectively allow social participation. This set of practices turns judicialization into an option for the realization of rights. This research was developed through empirical methodology, with a hypothetical-deductive method through bibliographic and documentary research, with analysis of the incident urban legislation and legal processes. The article is divided into two parts. The first presents the Niteroi scenario regarding processes with urban content; and, the second, the literature review on the judicialization of public policies.